2013
DOI: 10.1111/roie.12091
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Spillovers and Contagion from Mature to Emerging Stock Markets

Abstract: 4Non-technical summary 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 34 publications
2
47
0
1
Order By: Relevance
“…This infers existing evidence is also pertinent to forecast the future volatility for a long horizon as concluded in previous literature (e.g., Neaime 2016;Auer 2016;Guris, Sacildi 2016;Sarwar, Khan 2016;Beirne et al 2013;Wang et al 2005;Li, Majerowska 2008;etc.). The sum of GARCH coefficients for all the developed and emerging stock markets approaches to one that is the basic condition required for mean reversion process.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This infers existing evidence is also pertinent to forecast the future volatility for a long horizon as concluded in previous literature (e.g., Neaime 2016;Auer 2016;Guris, Sacildi 2016;Sarwar, Khan 2016;Beirne et al 2013;Wang et al 2005;Li, Majerowska 2008;etc.). The sum of GARCH coefficients for all the developed and emerging stock markets approaches to one that is the basic condition required for mean reversion process.…”
Section: Discussionsupporting
confidence: 87%
“…The research studies focusing on emerging equity markets such as, Neaime (2016), Auer (2016), Guris and Sacildi (2016), Sarwar and Khan (2016), Worthington and Higgs (2004), Wang et al (2005), Li and Majerowska (2008), Beirne et al (2013), andErb et al (1997). Among these studies, Wang et al (2005) conducted empirical analysis using EGARCH model found the confirmation of both returns and shock transmission from developed stock markets to emerging equity markets of the Asia.…”
Section: Theoretical Substantiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to volatility, much of the recent research on volatility spillovers employs versions of the GARCH model (for example Beirne et al, 2013;Li and Giles, 2015;and Lin, 2013, among others). However, the ability to measure spillovers by those types of models is limited, namely in their lack of spillover dynamics.…”
Section: Online Firstmentioning
confidence: 99%